2015
DOI: 10.1007/s00122-015-2591-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic approaches to selection in outcrossing perennials: focus on essential oil crops

Abstract: The yield of essential oil in commercially harvested perennial species (e.g. 'Oil Mallee' eucalypts, Tea Trees and Hop) is dependent on complex quantitative traits such as foliar oil concentration, biomass and adaptability. These often show large natural variation and some are highly heritable, which has enabled significant gains in oil yield via traditional phenotypic recurrent selection. Analysis of transcript abundance and allelic diversity has revealed that essential oil yield is likely to be controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 97 publications
(120 reference statements)
0
20
0
Order By: Relevance
“…GWAS provides potential capacity to identify the genes that are causally associated with phenotypes of focal traits, especially traits that are strongly affected by one or a few genes. However, it has been less successful in identifying such genes in species with phenotypes that are mostly influenced by numerous minor quantitative trait loci (QTLs) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…GWAS provides potential capacity to identify the genes that are causally associated with phenotypes of focal traits, especially traits that are strongly affected by one or a few genes. However, it has been less successful in identifying such genes in species with phenotypes that are mostly influenced by numerous minor quantitative trait loci (QTLs) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The obvious dosage effect showed that pyramiding these two O/B QTL and one or two of the O/DM QTL has great potential for oil palm breeding. Oil yield relative traits are complex and often controlled by large numbers of genetic loci with small additive effect [39], hence combining multiple QTL with beneficial genotypes in an individual can be an effective strategy of oil yield improvement in palm breeding.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, genetic and environmental factors regulate terpene biosynthesis at multiple levels, including transcription, protein accumulation, and posttranscriptional/translational regulation [29,61]. Understanding the molecular underpinnings of terpene metabolism in plants will benefit from a systems biology approach, where the goal is to quantitatively describe the cellular processes through global modeling of the interactions and dynamics of the molecular components.…”
Section: A Systems-level Understanding Of Terpene Biosynthesismentioning
confidence: 99%
“…For example, in a related tea tree, three cycles of phenotypic selection over 20 years resulted in doubling the oil yield from 148 to 300 kg ha -1 [87]. This process could be accelerated in undomesticated eucalypt species through molecular breeding techniques such as genomic selection [61]. Previous studies reported that the terpene content is limited by the storage gland capacity, which in turn is regulated by the leaf area and thickness [46].…”
Section: Commercialization Potential Of Terpenes From Plantsmentioning
confidence: 99%